Higher order genomic organization and regulatory compartmentalization for cell cycle control at the G1/S‐phase transition. Issue 10 (10th May 2018) - Ghule, Prachi N.; Seward, David J.; Fritz, Andrew J.; Boyd, Joseph R.; van Wijnen, Andre J.; Lian, Jane B.; Stein, Janet L.; Stein, Gary S.
Abstract : Fidelity of histone gene regulation, and ultimately of histone protein biosynthesis, is obligatory for packaging of newly replicated DNA into chromatin. Control of histone gene expression within the 3‐dimensional context of nuclear organization is reflected by two well documented observations. DNA replication‐dependent histone mRNAs are synthesized at specialized subnuclear domains designated histone locus bodies (HLBs), in response to activation of the growth factor dependent Cyclin E/CDK2/HINFP/NPAT pathway at the G1/S transition in mammalian cells. Complete loss of the histone gene regulatory factors HINFP or NPAT disrupts HLB integrity that is necessary for coordinate control of DNA replication and histone gene transcription. Here we review the molecular histone‐related requirements for G1/S‐phase progression during the cell cycle. Recently developed experimental strategies, now enable us to explore mechanisms involved in dynamic control of histone gene expression in the context of the temporal (cell cycle) and spatial (HLBs) remodeling of the histone gene loci. Abstract : Fidelity of histone gene regulation, and ultimately of histone protein biosynthesis, is obligatory for packaging of newly replicated DNA into chromatin. Control of histone gene expression within the 3‐dimensional context of nuclear organization is reflected by two well documented observations. DNA replication‐dependent histone mRNAs are synthesized at specialized subnuclear domains designated histone locus bodies (HLBs), in response to activation of the growth factor dependent Cyclin E/CDK2/HINFP/NPAT pathway at the G1/S transition in mammalian cells. Complete loss of the histone gene regulatory factors HINFP or NPAT disrupts HLB integrity that is necessary for coordinate control of DNA replication and histone gene transcription.